2020
DOI: 10.3892/etm.2020.9069
|View full text |Cite
|
Sign up to set email alerts
|

Multi‑slice spiral CT evaluation of chronic radiation colitis and rectitis

Abstract: The aim of the present study was to retrospectively analyse the multi-slice spiral CT (MSCT) findings of radiation colitis and rectitis (RC&R). A total of 23 cases of RC&R detected by helical CT were included. The CT findings and clinical and endoscopy data of the patients were reviewed. The primary tumours included cancers of the cervix (n=17), rectum (n=4), ovaries (n=1) and bladder (n=1). The total dose of radiation per patient was 46-60 Gy (mean, 49.7 Gy) delivered over 5 weeks. The CT manifestations inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…MSCT can also evaluate vascular supply and vasodilation of the intestines, which are important factors in the development of fibrosis. In MSCT examinations, findings such as increased bowel wall thickness, luminal stenosis, and mural stratification are indicative of fibrosis 33,34 . Moreover, the presence of engorged vasa recta and pericentric fat stranding may suggest the severity of fibrosis 35 .…”
Section: Discussionmentioning
confidence: 99%
“…MSCT can also evaluate vascular supply and vasodilation of the intestines, which are important factors in the development of fibrosis. In MSCT examinations, findings such as increased bowel wall thickness, luminal stenosis, and mural stratification are indicative of fibrosis 33,34 . Moreover, the presence of engorged vasa recta and pericentric fat stranding may suggest the severity of fibrosis 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Also, for case selection, the disease types for the two methods (FTRs and SRs) were basically similar. Also, we included patients who had no surgical indications (e.g., mesenteric vascular disease, non-strangulated intestinal obstruction, and inflammatory bowel disease), and surgical pathology as the gold standard was not performed for these patients, although previous studies have demonstrated that clinical data, biochemical indicators, and imaging data can be used as diagnostic standards (28)(29)(30)(31); to ensure a more reliable accuracy evaluation, these patients should be excluded. Second, pretreatment preparation, scanning techniques, and individual differences between patients could partially influence the manifestations of SBDs, and perfect intestinal filling and excellent image quality were not guaranteed for all patients in this study.…”
Section: Discussionmentioning
confidence: 99%